Dynamic changes of rumen bacteria and their fermentative ability in high-producing dairy cows during the late perinatal period - Mao, Yongxia; Wang, Feifei; Kong, Weiyi; Wang, Ruiling; Liu, Xin; Ding, Hui; Ma, Yun; Guo, Yansheng (Frontiers in Microbiology, 2023)
High-producing dairy cows face varying degrees of metabolic stress and challenges during late perinatal period, resulting in ruminal bacteria abundance and their fermentative ability occur a series of changes. However, the dynamic changes are still not clear. Ten healthy, high-producing Holstein dairy cows with similar body condition and the same parity were selected, and ruminal fluids from the dairy cows at postpartum 0 d, 7 d, 14 d and 21 d were collected before morning feeding. 16S rRNA highthroughput sequencing, GC-MS/MS targeted metabolomics and UPLC-MS/MS untargeted metabolomics were applied in the study to investigated the dynamic changes within 21 d postpartum. The results displayed that the structures of ruminal bacteria were significantly altered from 0 ~ 7 d postpartum (R=0.486，P=0.002), reflecting by the significantly declining abundances of Euryarchaeota and Chloroflexi phyla, Christensenellaceae, Methanobrevibacter and Flexilinea genera (P < 0.05), and the obviously ascending abundances of Ruminococcaceae, Moryella, Pseudobutyrivibrio and Prevotellaceae genera at 7 d postpartum (P < 0.05); that the structures of ruminal bacteria were significantly also varied from 7 ~ 14 d postpartum (R=0.125，P=0.022), reflecting by the reducing abundances of Christensenellaceae, Ruminococcaceae and Moryella genera (P<0.05), and the elevating abundances of Sharpea and Olsenella genera at 14 d postpartum (P<0.05); that the metabolic profiles of ruminal SCFAs were obviously varied from 0 ~7 d postpartum, resulting by the higher levels of propionic acid, butyric acid and valeric acid at 7 d postpartum (P<0.05); that the metabolic profiles of other ruminal metabolites were significantly shifted from 0~ d postpartum, with 27 significantly elevated metabolites and 35 apparently reduced metabolites (P<0.05). The correlation analysis indicated that propionic acid was positively correlated with Prevotellaceae and Ruminococcaceae (P<0.05), negatively with Methanobrevibacter (P<0.01), butyric acid was positively associated with Prevotellaceae, Ruminococcaceae and Pseudobutyrivibrio (P<0.05), negatively with Christensenellaceae (P<0.01), valeric acid was positively linked with Prevotellaceae and Ruminococcaceae (P<0.05), pyridoxal was positively correlated with Flexilinea and Methanobrevibacter (P<0.05), negatively with Ruminococcaceae (P<0.01), tyramine was negatively linked with Ruminococcaceae (P<0.01). The findings contribute to the decision of nutritional management and prevention of metabolic diseases in high-producing dairy cows during late perinatal period.